Understanding and Addressing Social Stigma Against Children with Intellectual Disabilities: Impact, Causes, and Strategies for Inclusion - Alyana Nur Fadillah; Ridyah Syifani Rahmah; Nurlaila Arifa Putri; Syaima Syafei; Nafisa Amelia Putri; Citra Ashri Maulidina; Mohammad Arif Taboer (International Disability Innovation Journal, 2025)
Social stigma against children with intellectual barriers is still a serious problem at various levels of society. Intellectual barriers are often seen as absolute weaknesses, leading to discrimination, social rejection, and limited access to education and an inclusive environment. This research aims to identify the forms of stigma that arise, the factors that influence them, and their impact on the psychosocial development of children and their families. The method used is a literature study with a qualitative approach. The results of the study show that stigma arises from a lack of understanding, cultural influences, and deeply rooted negative stereotypes. This stigma not only hinders children's growth and development, but also reduces parents' confidence in accompanying their children. Therefore, a comprehensive strategy is needed that includes public education, the implementation of inclusive policies, and the empowerment of families and schools in creating an environment that accepts and supports children with intellectual disabilities. Efforts to eliminate stigma are the first step towards a more just, inclusive, and humane society for children with intellectual barriers.